2018
DOI: 10.1016/j.jmoldx.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Standards and Guidelines for Validating Next-Generation Sequencing Bioinformatics Pipelines

Abstract: Bioinformatics pipelines are an integral component of next-generation sequencing (NGS). Processing raw sequence data to detect genomic alterations has significant impact on disease management and patient care. Because of the lack of published guidance, there is currently a high degree of variability in how members of the global molecular genetics and pathology community establish and validate bioinformatics pipelines. Improperly developed, validated, and/or monitored pipelines may generate inaccurate results t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
137
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 373 publications
(139 citation statements)
references
References 43 publications
1
137
0
1
Order By: Relevance
“…In our experience, the use of selected NGS panels is useful and easy to handle for rapid diagnosis in clinically and immunologically wellcharacterized phenotypes. As compared to WES, targeted small NGS panels provide an important alternative for clinicians for direct sequencing of relevant genes, guaranteeing a high coverage and sequencing depth (64). On the contrary, their application in patients with atypical phenotypes could result in an incomplete and delayed diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experience, the use of selected NGS panels is useful and easy to handle for rapid diagnosis in clinically and immunologically wellcharacterized phenotypes. As compared to WES, targeted small NGS panels provide an important alternative for clinicians for direct sequencing of relevant genes, guaranteeing a high coverage and sequencing depth (64). On the contrary, their application in patients with atypical phenotypes could result in an incomplete and delayed diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many previously undetected variants do not have a well-defined role in our genome (1.5 × 10 6 million variants in each genome and lesser in exome). In this scenario, ethical and legal issues related to the disclosure of genetic information generated by NGS need to be considered and guidelines should be developed to help the different specialists to translate the genetic results into the clinics (64).…”
Section: Discussionmentioning
confidence: 99%
“…Most laboratories used an Illumina (San Diego, CA) platform with hybridization-based targeting. One workflow (6) used whole-genome sequencing and another (8) used the Ion Torrent platform with AmpliSeq PCR-based targeting (ThermoFisher, Waltham, MA). Each workflow used a unique bioinformatics pipeline, including custom software, thirdparty software, and sequencing vendor-supplied software (Supplemental Methods).…”
Section: Methodsmentioning
confidence: 99%
“…A recent systematic review found a "high degree of variability" among published validation studies, some of which did not even stratify performance by variant type (i.e. SNV versus indel) [8]. Indeed, the 2017 AMP (Association for Molecular Pathology) and CAP (College of American Pathologists) guidelines for NGS bioinformatics recommend that at least 59 variants of each type be included in validation studies [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation